Autogenous bone augmentation from the zygomatic alveolar crest: a volumetric retrospective analysis in the maxilla - Irina Kuster; Livia Osterwalder; Silvio Valdec; Bernd Stadlinger; Maximilian E. H. Wagner; Martin Rücker; Dominique Bichsel (SpringerOpen, 2020)
Abstract Background Autogenous bone augmentation is the gold standard for the treatment of extended bone defects prior to implantation. Bone augmentation from the zygomatic crest is a valuable option with several advantages, but the current literature for this treatment is scant. The aim of this study was to evaluate the increase in bone volume after locoregional bone augmentation using autogenous bone from the zygomatic alveolar crest as well as the complications and success rate. Results Analysis of the augmented bone volume in seven patients showed a maximum volume gain of 0.97 cm3. An average of 0.54 cm3 of autogenous bone (SD 0.24 cm3; median: 0.54 cm3) was augmented. Implantation following bone augmentation was possible in all cases. Complications occurred in three patients. Conclusion The zygomatic alveolar crest is a valuable donor site for autogenous alveolar onlay grafting in a locoregional area such as the maxillary front. Low donor site morbidity, good access, and its suitable convexity make it a beneficial choice for autogenous bone augmentation.